ACT-10 TREATMENT FOR GLIOBLASTOMA RECURRED AFTER CONCOMITANT CHEMORADIATION THERAPY WITH TEMOZOLOMIDE AND THEIR PROGNOSIS. (16th December 2019) - Mori, Kanji; Shofuda, Tomoko; Mano, Masayuki; Kodama, Yoshinori; Kinoshita, Manabu; Arita, Hideyuki; Moriuchi, Shusuke; Uda, Takehiro; Taki, Takuyu; Fukai, Junya; Nonaka, Masahiro; Ishibashi, Kenichi; et al.
Abstract: There are few data about treatment for glioblastoma recurred after concomitant chemoradiation therapy with temozolomide (TMZ). We retrospectively examined treatment and prognosis of recurred glioblastoma patients who registered Kansai molecular diagnosis network for central nervous system tumors, and whose clinical information were available. One hundred and fifty-seven patients that were clinically diagnosed as recurrence between November 2007 and April 2019 were included. Their median age at primary diagnosis was 52 years old and median KPS was 80%. Proportion of methylated MGMT promoter was 43.3% (65 patients), and mutated IDH was 5.4% (8 patients). Median overall survival after recurrence (mSAR) was 8.2 months. One hundred and sixteen patients (73.9%) were received any anticancer treatment and their mSAR was 10.5m. Combination of TMZ and bevacizumab (Bev) were most frequently used for 33 patients, followed by Bev monotherapy for 17 patients, surgery + TMZ + Bev for 15 patients, surgery + TMZ for 12 patients, and TMZ monotherapy for ten. Their mSAR were 8.0m, 7.5m, 10.5m, 13.0m, and 8.0m, respectively. Using univariate analysis, MGMT promoter methylation (p=0.0007), TMZ (p=0.00933), surgery (p=0.0126), re-radiation (p=0.0367), and surgery+TMZ+Bev (p=0.0493) significantly affected prognosis. By multivariate analysis, MGMT promoter methylation, TMZ, and re-radiation were statistically significant (p=0.000138, 0.00161, 0.00403, respectively). These data showed that relatively young patients with good performance status would receive anti-cancer treatment beyond progression and MGMT promoter methylation might be one of prognostic factor for longer survival. In this cohort, re-radiation was performed for few patients and nitrosourea such as nimustine was almost not used. Further study would be needed whether these treatments have any positive effect or not.